Aplikasi Soal Ujian Seleksi Peserta Pelatihan Kejuruan Operator Komputer Berbasis Multimedia Untuk Mendukung Konsep â€œPaperless Officeâ€ Di PPKD Jakarta Timur - Pamungkas, Petrus Dwi Ananto; Wicaksono, Harjunadi; Septanto, Henri (BINA INSANI ICT JOURNAL; Vol 2 No 1 (2015): Bina Insani ICT Journal (Maret 2015), 2015)
Abstract: Information and Communication Technology plays a major role in education and training. The impact of these developments can be seen with the heavy use of multimedia applications and devices that are used in teaching and learning. Teaching materials from the subject matter until the exam has started a lot is made in the form of multimedia applications. Exam is one measure the success of teaching and learning activities, though the test results are not the only measure of the success of the teacher / lecturer / instructor / trainer and other teachers. The common problem that occurs is the teacher / lecturer / instructor / trainer and other teachers sometimes hit a problem of time in examinations exam results, besides the question paper and answer sheets can also be a waste of paper because it can not be used again on the next exam. Wasteful use of paper at the present time is contrary to the implementation of paperless office is starting a lot of formal adoption by many government and private institutions. The use of multimedia-based exam application and paperless movement that has been applied in many institutions with a wide range of issues and challenges to inspire writers to make this article. This article was written based on the research that has been done in PPKD East Jakarta in 2014. The aim of this study is to support the implementation of Paperless Office motion so that the test execution selection of trainees to be more efficient in terms of time and cost. Keywords: paperless office, multimedia, applications, test Abstrak: Perkembangan Teknologi Informasi dan Komunikasi berperan besar dalam dunia pendidikan dan pelatihan. Dampak dari perkembangan tersebut dapat dilihat dengan banyaknya  penggunaan aplikasi dan perangkat multimedia yang digunakan dalam kegiatan belajar mengajar. Bahan ajar mulai dari materi pelajaran sampai dengan ujian saat ini mulai banyak dibuat dalam bentuk aplikasi multimedia. Ujian adalah salah satu alat ukur keberhasilan kegiatan belajar mengajar, meskipun demikian hasil ujian bukan satu-satunya alat ukur keberhasilan guru/dosen/instruktur/trainer dan pengajar lainnya. Masalah umum yang terjadi adalah para guru/dosen/instruktur/trainer dan pengajar lainnya kadang-kadang terbentur masalah waktu dalam melakukan pemeriksaan hasil ujian, selain itu kertas soal dan kertas jawaban juga dapat menjadi limbah kertas karena tidak dapat digunakan lagi pada ujian berikutnya. Pemborosan penggunaan kertas di masa sekarang ini bertentangan dengan penerapan paperless office yang saat ini sudah mulai banyak diterapkan secara resmi oleh banyak lembaga pemerintah maupun swasta. Penggunaan aplikasi soal ujian berbasis multimedia serta gerakan paperless yang sudah diterapkan di banyak lembaga dengan berbagai masalah dan tantangan menginspirasi penulis untuk membuat artikel ini. Artikel ini ditulis berdasarkan penelitian yang telah dilakukan di PPKD Jakarta Timur pada tahun 2014. Tujuan dari penelitian ini adalah untuk mendukung implementasi gerakan Paperless Office sehingga pelaksanaan ujian seleksi peserta pelatihan menjadi lebih efisien dari sisi waktu dan biaya. Kata kunci: paperless office, multimedia, aplikasi, ujian